2016
DOI: 10.3146/0095-3679-43.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping Peanut Genotypes for Drought Tolerance

Abstract: Drought and heat stress can result in aflatoxin contamination of peanuts especially when this occurs during the last three to six wk of the growing season. Identifying drought-tolerant genotypes may aid in development of peanuts that are less susceptible to aflatoxin contamination. Research was conducted to phenotype seven peanut genotypes based on their response to drought stress. Six peanut genotypes that have exhibited lower aflatoxin and/or drought tolerance in previous researches (Tifguard, Tifrunner, Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Nageswara Rao et al [7] also reported similar specific leaf area between peanut genotypes. These physiological traits (LAI, CT, SCMR, and NDVI) are important in improving productivity and are used as indirect indices for improving drought tolerance in peanut [8]. Traits such as SCMR and NDVI determine the photosynthetic potential of plants and have been reported to be highly associated with yield and can be effective as in-season predictors of yield [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nageswara Rao et al [7] also reported similar specific leaf area between peanut genotypes. These physiological traits (LAI, CT, SCMR, and NDVI) are important in improving productivity and are used as indirect indices for improving drought tolerance in peanut [8]. Traits such as SCMR and NDVI determine the photosynthetic potential of plants and have been reported to be highly associated with yield and can be effective as in-season predictors of yield [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll content and fluorescence parameters determine the integrity of the internal apparatus for photosynthesis and provide a precise platform for detection and quantification of plant tolerance to drought stress [6] and were speculated as a useful indicator for photosynthetic capacity in groundnut [7]. Canopy temperature (CT) was reported to be a marker for drought tolerance through its negative correlation with transpiration cooling and carbon dioxide exchange rate [8]. Genotypes that maintain cooler canopies under stress conditions possess a high potential for water stress tolerance and high yield [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations